Efektivitas manajemen risiko terhadap ketidakpastian imbal hasil dalam akad salam pada perbankan syariah - nisa, fitria izzatun (Maliki Interdisciplinary Journal, 2025)
Akad Salam is one of the financing instruments in Islamic banking that has great potential to support the agricultural sector and commodity production. In this contract, payment is made in advance for goods that are handed over later, thus providing initial liquidity for the producer. Although in accordance with sharia principles, the implementation of the salam contract faces significant challenges, especially related to uncertainty of returns due to internal and external factors such as weather, price fluctuations, and moral hazards. This study aims to analyze the effectiveness of risk management in dealing with such uncertainties and identify obstacles and strategic solutions. The results of the analysis show that the implementation of risk management in the salam contract is still not optimal, especially due to technological constraints, low financial literacy, and the lack of integrated information systems.